Tren Penelitian Pendidikan Ekonomi Keluarga di Indonesia: Sebuah Analisis Bibliometrik - Ginanjar, Ardhita Eko; Prakoso, Albrian Fiky (Kayon Media, 2024)
Abstract: Family economic education is important to support the survival of individuals in the economic aspect in the era of Society 5.0. This affects the development of related research. This study aims to illustrate the scheme in research and elaborate on topics related to family economic education in Indonesia. Bibliometric analysis is used in research to map related literature from 2019 to June 2024. The data sources in this research are Scopus and Google Scholar. With the help of VosViewer and Publish or Perish software, 33 articles suitable for the research context were obtained. The results imply that family economic education in Indonesia fluctuates according to existing economic conditions. Abstrak: Pendidikan ekonomi keluarga penting guna menunjang keberlangsungan hidup individu dalam aspek ekonomi di era society 5.0. Hal tersebut mempengaruhi perkembangan riset terkait. Penelitian ini bertujuan guna mengilustrasikan skema dalam riset dan elaborasi topik terkait dengan pendidikan ekonomi keluarga di Indonesia. Analisis bibliometrik dimanfaatkan dalam riset guna memetakan literatur terkait mulai dari tahun 2019 hingga Juni 2024. Sumber data dalam riset ini ialah Scopus dan Google Scholar. Dengan bantuan software VosViewer dan Publish or Perish, didapatkan 33 artikel yang sesuai konteks riset. Hasil yang didapat berimplikasi bahwa topik pendidikan ekonomi keluarga di Indonesia mengalami fluktuasi sesuai dengan kondisi perekonomian yang ada